Ceraphronoid Wasps (Hymenoptera, Ceraphronoidea) of the Fauna of the Ukraine. Communication 1 - Alekseev, V.N.; Radchenko, T.D. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2001)
A brief review of cerafronoid wasps of the Ukrainian fauna is given. Keys to families, subfamiles, genera, and species of the family Megaspilidae (except for the genus Conostigmus) known from Ukraine is provided.